Comparative effectiveness of ventricular tachycardia ablation vs. escalated antiarrhythmic drug therapy by location of myocardial infarction: a sub-study of the VANISH trial. Issue 6 (29th December 2021) - Samuel, Michelle; Rivard, Lena; Nault, Isabelle; Gula, Lorne; Essebag, Vidal; Parkash, Ratika; Sterns, Laurence D; Khairy, Paul; Sapp, John L
Abstract: Aims: Complexity of the ventricular tachycardia (VT) substrate and the size and thickness of infarction area border zones differ based on location of myocardial infarctions (MIs). These differences may translate into heterogeneity in the effectiveness of treatments. This study aims to examine the influence of infarct location on the effectiveness of VT ablation in comparison with escalated pharmacological therapy in patients with prior MI and antiarrhythmic drug (AAD)-refractory VT. Methods and results: VANISH trial participants were categorized based on the presence or absence of an inferior MI scar. Inverse probability of treatment weighted Cox models were calculated for each subgroup. Of 259 randomized patients (median age 69.8 years, 7.0% women), 135 had an inferior MI and 124 had a non-inferior MI. Among patients with an inferior MI, no statistically significant difference in the composite primary outcome of all-cause mortality, appropriate implantable cardioverter-defibrillator (ICD) shock, and VT storm was detected between treatment arms [adjusted hazard ratio (aHR) 0.80, 95% confidence interval (CI) 0.51–1.20]. In contrast, patients with non-inferior MIs had a statistically significant reduction in the incidence of the primary outcome with ablation (aHR 0.48, 95% CI 0.27–0.86). In a sensitivity analysis of anterior MI patients ( n = 83), a trend towards a reduction in the primary outcome with ablation was detected (aHR 0.50, 95% CI 0.23–1.09). Conclusion: The effectiveness of VT ablation versus escalated AADs varies based on the location of the MI. Patients with MI scars located only in non-inferior regions of the ventricles derive greater benefit from VT ablation in comparison to escalation of AADs in reducing VT-related events.